CT virtual endoscopy and 3D stereoscopic visualisation in the evaluation of coronary stenting - Sun, Zhonghua; Lawrence-Brown, Michael (University of Malaya, 2009)
The aim of this case report is to present the additional value provided by CT virtual endoscopy and 3D stereoscopic visualisation when compared with 2D visualisations in the assessment of coronary stenting. A 64-year old patient was treated with left coronary stenting 8 years ago and recently followed up with multidetector row CT angiography. An in-stent restenosis of the left coronary artery was suspected based on 2D axial and multiplanar reformatted images. 3D virtual endoscopy was generated to demonstrate the smooth intraluminal surface of coronary artery wall, and there was no evidence of restenosis or intraluminal irregularity. Virtual fly-through of the coronary artery was produced to examine the entire length of the coronary artery with the aim of demonstrating the intraluminal changes following placement of the coronary stent. In addition, stereoscopic views were generated to show the relationship between coronary artery branches and the coronary stent. In comparison with traditional 2D visualisations, virtual endoscopy was useful for assessment of the intraluminal appearance of the coronary artery wall following coronary stent implantation, while stereoscopic visualisation improved observers? understanding of the complex cardiac structures. Thus, both methods could be used as a complementary tool in cardiac imaging.